(untitled) (International Journal of Current Engineering and Technology, 2015)
Among the various mechanical power transmission means, gears are the most rugged and durable, but proper designing of the gears is a challenging task. It is expected to follow the pertinent standards of AGMA (American Gear Manufacturing Association) to design a reliable gear. These standards include a large number of empirical design factors accounting for various uncertainties. Due to subjective nature of those factors, often wrong input design factors lead to over-design or under-design of the gear. A portion of the present study is to analyze the various correction factors used in AGMA equations. To decide the appropriate values of correction factors, it is advisable to account statistical variations in operating and geometric conditions in the form of their mean and standard deviation values. In the present work, a methodology of probabilistic design of spur gear has been presented. A case study has been detailed to compare the procedure suggested by AGMA standard and the proposed methodology.